2004
DOI: 10.1002/humu.20028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mutation in the coding region of the grey-lethal geneOSTM1in human malignant infantile osteopetrosis

Abstract: Autosomal recessive malignant infantile osteopetrosis (ARO) is characterized by severe osteosclerosis, pathologic fractures, hepatosplenomegaly, and pancytopenia. The pathophysiological basis is inadequate bone resorption due to osteoclast dysfunction. In the majority of cases, mutations in either of two human genes cause this fatal disorder: TCIRG1, encoding a subunit of the osteoclast H(+)-ATPase, and the voltage-gated chloride channel gene CLCN7. We excluded both genes in a small inbred family with malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…The α 3 subunit of the H + ATPase, encoded by the TCIRG1 gene, is involved in the transportation of these protons through the ruffled border into the resorption lacuna (3,4), while chloride channel 7 (CLC7), encoded by the CLCN7 gene, translocates chloride ions to maintain electroneutrality (5)(6)(7). Finally, the OSTM1 gene encodes a type I transmembrane protein with E3 ubiquitin ligase activity (8)(9)(10)(11). The exact function of Ostm1 remains elusive, but a recent report identified the Ostm1 protein as a β subunit of CLC7 and demonstrated that it requires CLC7 to localize to lysosomes (12).…”
Section: Introductionmentioning
confidence: 99%
“…The α 3 subunit of the H + ATPase, encoded by the TCIRG1 gene, is involved in the transportation of these protons through the ruffled border into the resorption lacuna (3,4), while chloride channel 7 (CLC7), encoded by the CLCN7 gene, translocates chloride ions to maintain electroneutrality (5)(6)(7). Finally, the OSTM1 gene encodes a type I transmembrane protein with E3 ubiquitin ligase activity (8)(9)(10)(11). The exact function of Ostm1 remains elusive, but a recent report identified the Ostm1 protein as a β subunit of CLC7 and demonstrated that it requires CLC7 to localize to lysosomes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Severe autosomal recessive osteopetrosis is a genetic disorder caused by mutations in several genes affecting osteoclast function, leading to fragile bones and increased infection rates [16,17]. Recently, defects in the OSTM1 gene have been found to generate ARO, both in humans and in the spontaneous grey-lethal mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with autosomal recessive osteopetrosis suffer from frequent fractures, hepatosplenomegaly and bone marrow obliteration, leading to early mortality unless treated with bone marrow transplantation [16,17]. Mutations in two human genes, TCIRG1 and CLCN7 (which encodes the ClC-7 protein), together are known to cause ~60% of autosomal recessive osteopetrosis cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subset of patients (5% in our cohort) displaying mutations in OSTM1 gene, encoding for a protein involved in late endosomal-lysosomal trafficking, functionally and physically linked to ClCN7 (Lange et al 2006;Meadows et al 2007), is characterized by even more serious neurological defects (neurodegeneration, optic atrophy, microcephaly, cortical atrophy; in one case, bilateral atrial subependymal heterotopias) (Chalhoub et al 2003;Quarello et al 2004;Ramirez et al 2004;Pangrazio et al 2006;Castellano Chiodo et al 2007;Maranda et al 2008). These findings strongly discourage HSCT, because, even if the transplant engrafted, the patient would die due to the severe CNS defects; indeed, in our series no OSTM1-dependent patients have been transplanted.…”
Section: Treating Human Aro: the Osteoclast-rich Formsmentioning
confidence: 96%